A Stand‐Alone Si‐Based Porous Photoelectrochemical Cell. Issue 19 (27th March 2019) - Vijselaar, Wouter J. C.; Perez‐Rodriguez, Paula; Westerik, Pieter J.; Tiggelaar, Roald M.; Smets, Arno H. M.; Gardeniers, Han; Huskens, Jurriaan
Abstract: Wireless photoelectrochemical (PEC) devices promise easy device fabrication as well as reduced losses. Here, the design and fabrication of a stand‐alone ion exchange material‐embedded, Si membrane‐based, photoelectrochemical cell architecture with micron‐sized pores is shown, to overcome the i) pH gradient formation due to long‐distance ion transport, ii) product crossover, and iii) parasitic light absorption by application of a patterned catalyst. The membrane‐embedded PEC cell with micropores utilizes a triple Si junction cell as the light absorber, and Pt and IrO x as electrocatalysts for the hydrogen evolution reactions and oxygen evolution reactions, respectively. The solar‐to‐hydrogen efficiency of 7% at steady‐state operation, as compared to an unpatterned ηPV of 10.8%, is mainly attributed to absorption losses by the incorporation of the micropores and catalyst microdots. The introduction of the Nafion ion exchange material ensures an intrinsically safe PEC cell, by reducing the total gas crossover to <0.1%, while without a cation exchange membrane, a crossover of >6% is observed. Only in a pure electrolyte of 1m H2 SO4, a pH gradient‐free system is observed thus completely avoiding the build‐up of a counteracting potential. Abstract : A triple junction Si photovoltaic cell is converted into a stand‐alone microporous photoelectrochemical cell with a solar‐to‐hydrogen efficiency of 7% with a stability >40 days. Micropores introduced into a photoelectrochemical cell mitigate ionic resistances caused by long proton diffusion distances between anode and cathode. A Nafion membrane in the micropores ensures O2 ‐H2 gas separation between compartments.